Insect threatens crops in Mauritania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The pink stemborer (Sesamia calamistis), a gnawing insect that attacks cereals, is currently responsible for the loss of 10,000 t of sorghum per year in the country. The stemborer is also a vector of a pathogen that destroys the stalks and panicles...